Analisis Pengaruh Pertumbuhan Ekonomi, Pengangguran, dan Kemiskinan terhadap Indeks Pembangunan Manusia Di Kabupaten Bojonegoro - Kurnia Sari Dewi; Wiwin Priana Primandhana; Mohammad Wahed (Ridwan Institute, 2021)
The study was conducted with the aim of knowing the effect of economic growth, unemployment, poverty on the Human Development Index (HDI) in Bojonegoro Regency for the period 2002 to 2019. Secondary data for this research were obtained through the websites of the East Java and Bojonegoro Central Statistics Agency (BPS). Quantitative research methods are used and use Multiple Linear Regression Analysis with the Ordinary Least Square (OLS) model. It can be concluded that economic growth does not have a significant effect on the HDI of Bojonegoro Regency. It is known that based on tcount less than ttable (0.861 ≤ 1.761), besides that, it is seen from the significance level, namely 0.404. Unemployment has not been able to significantly influence HDI in Bojonegoro Regency with the t value less than t table (1.137 ≤ 1.761). while poverty can significantly affect HDI in Bojonegoro Regency, seen from the value of t count more than t table (3.404 ≥ 1.761).